2006
DOI: 10.1182/blood-2005-11-012450
|View full text |Cite
|
Sign up to set email alerts
|

Gender imbalance and risk factor interactions in heparin-induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia (HIT)is caused by antibodies against a "self" protein-platelet factor 4-bound to heparin. We observed an overrepresentation of the female gender in 290 patients who developed HIT after cardiac or orthopedic surgery compared with the representation found in national databases (study 1). Therefore, we investigated gender imbalance in HIT by logistic regression analysis of a randomized controlled trial of unfractionated heparin (UFH) and lowmolecular-weight heparin (LMWH) (study 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
4
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(178 citation statements)
references
References 41 publications
9
150
4
4
Order By: Relevance
“…The frequency of forming anti-PF4/heparin antibodies, as well as the risk of clinical HIT itself, varies considerably in different clinical settings [2]. One relevant factor is the type of heparin: for example unfractionated heparin (UFH) is more immunogenic, and is associated with a higher risk of HIT, compared with low-molecular weight heparin (LMWH) [3,4]. However, certain observations suggest that non-drug factors could also influence risk of HIT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of forming anti-PF4/heparin antibodies, as well as the risk of clinical HIT itself, varies considerably in different clinical settings [2]. One relevant factor is the type of heparin: for example unfractionated heparin (UFH) is more immunogenic, and is associated with a higher risk of HIT, compared with low-molecular weight heparin (LMWH) [3,4]. However, certain observations suggest that non-drug factors could also influence risk of HIT.…”
Section: Introductionmentioning
confidence: 99%
“…However, certain observations suggest that non-drug factors could also influence risk of HIT. For example, one meta-analysis [4] found that postsurgery patients are more likely than medical patients to develop HIT, and another study [5] reported that pregnant women are less likely than non-pregnant females to develop HIT.…”
Section: Introductionmentioning
confidence: 99%
“…Bizim olgumuzda olduğu gibi kadın cinsiyet HBT riskini artırmaktadır. Ayrıca, dört günden fazla heparin kullanımının da 20 kata kadar HBT riskini artırmakta olduğu bildirilmektedir (10). Bizim olgumuza bakıldığında HBT gelişimi için bütün riskleri taşıdığı görülmektedir.…”
Section: Discussionunclassified
“…Specifinis gydymas taip pat nereikalingas. Šią trombocitopeniją sąlygoja tiesioginė sąveika tarp heparino ir trombocitų, sukelianti pastarųjų susigrupavimą ar suirimą (11)(12)(13).…”
Section: Tęstinės Medicinos Studijosunclassified
“…Genetiniai trombozės rizikos veiksniai, tokie kaip faktorius V Leiden, protrombino geno mutacija, metilenetetrahidrofolato reduktazės (MTHFR) polimorfizmas ir trombocitų receptorių polimorfizmas su HIT susijusios trombozės rizikos nedidina (12,22 Trombocitopenija būna vidutinio dydžio, apie 50-60×10 9 /l. 90 proc.…”
Section: Etiologija Dažnisunclassified